Perkembangan Hukum Islam di Indonesia - Ahmad Badrut Tamam (Proceedings of Annual Conference for Muslim Scholars, 2018)
Islamic law has long lived in the legal consciousness of Islamic society in Indonesia along with the growth and development of Islam. But since the arrival of the colonial, Islamic law has ups and downs. The enactment of Islamic law in Indonesia at this time is often not based solely on what actually takes place in society, but rather shows its form as a result of social construction created by colonists, with a view to achieving certain goals. As the antitheses of the colonial policy, various theories of the enforcement of Islamic law were sparked by Indonesian scholars, who initially aimed at resisting colonial policies. Post-independence, along with the development of the times, several theories of the enforcement of Islamic law was emerging.